2019
DOI: 10.26504/qec2019sum_sa_lynch
|View full text |Cite
|
Sign up to set email alerts
|

Carbon taxation in Ireland: distributional effects of revenue recycling policies

Abstract: We calculate the impact of an increase in carbon taxation on carbon emissions and on income inequality. Carbon emissions reduce by 3.94 per cent for a carbon tax increase of €30 per tonne, and 10.24 per cent for an increase of €80 per tonne. Carbon taxation is found to be regressive, with poorer households spending a greater proportion of their income on the tax than more affluent households. However, returning the carbon tax revenues to households reverses this regressive effect, and the net policy effect is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…It does so using the latest version of SWITCH -the ESRI's tax and benefit microsimulation model -which has been updated so that the sample of households it runs on is representative of the 2020 population post-COVID related job losses. Previous work has shown that the same outcome can be achieved in more normal times without exhausting revenues raised by the tax, through a combination of social welfare increases and tax cuts (Bercholz and Roantree, 2019;Tovar-Reaños and Lynch, 2019;Callan et al, 2009;Healy, 2003;Clinch and Healy, 2000).…”
Section: Chapter 5 Conclusionmentioning
confidence: 86%
“…It does so using the latest version of SWITCH -the ESRI's tax and benefit microsimulation model -which has been updated so that the sample of households it runs on is representative of the 2020 population post-COVID related job losses. Previous work has shown that the same outcome can be achieved in more normal times without exhausting revenues raised by the tax, through a combination of social welfare increases and tax cuts (Bercholz and Roantree, 2019;Tovar-Reaños and Lynch, 2019;Callan et al, 2009;Healy, 2003;Clinch and Healy, 2000).…”
Section: Chapter 5 Conclusionmentioning
confidence: 86%
“…Although this may reduce the scale of losses relative to those estimated here, it is unlikely to alter the pattern of these losses unless the magnitude of responses also differs significantly by income level or household type. Forthcoming work by researchers at the ESRI (Tovar Reaños and Lynch, 2019) suggests that -at least on the expenditure side -this is unlikely to be the case. They estimate that the pattern of losses from the higher carbon tax as a share of disposable income looks very similar to that shown in Figure 2 even after accounting for changes in demand for these goods.…”
Section: Appendixmentioning
confidence: 99%